2021
DOI: 10.1002/jcph.1965
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and the Risk of Anemia of Advanced Chronic Kidney Disease in Patients With Type 2 Diabetes Mellitus

Abstract: This retrospective cohort study determines whether metformin monotherapy or combination therapies can decrease anemia risk in the progress of advanced chronic kidney disease for patients with type 2 diabetes mellitus. The data set was obtained from the National Health Insurance Research Database, containing 1 million randomly selected beneficiaries. After matching, 9303 pairs (1:1) of metformin users and nonusers were acquired. Every patient was individually recorded from 1997 to 2012 to identify anemia incide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Metformin might cause intestinal malabsorption, preventing the absorption of Vitamin B12. 27 Inflammation and renal tubular injury may also play a role in the pathogenesis of anemia. A prior study reported that interstitial lesions, rather than glomerular lesions, were a significant predictor of renal prognosis in patients with diabetic nephropathy, type 2 diabetes, and massive proteinuria.…”
Section: Discussionmentioning
confidence: 99%
“…Metformin might cause intestinal malabsorption, preventing the absorption of Vitamin B12. 27 Inflammation and renal tubular injury may also play a role in the pathogenesis of anemia. A prior study reported that interstitial lesions, rather than glomerular lesions, were a significant predictor of renal prognosis in patients with diabetic nephropathy, type 2 diabetes, and massive proteinuria.…”
Section: Discussionmentioning
confidence: 99%